Enhanced Performance of Constant Frequency Torque Controller-Based Direct Torque Control of Induction Machines with Increased Torque-Loop Bandwidth - Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2020)
Constant frequency torque controller-based direct torque control (CFTC-DTC) is emerging as a powerful control strategy for a high-performance control of alternating-current motor drives. Compared to DTC, the CFTC-DTC has less torque and flux ripples with a fixed switching frequency. Nevertheless, it has a limitation of the torque-loop bandwidth, as it uses the sampling frequency from a digital signal processor to generate a triangular-based carrier. The switching frequency of the control system is determined by the carrier frequency of the CFTC. The frequency limitation of CFTC leads to sector-flux droop, which causes a distortion in the motor phase current and aggravation in the torque and speed waveforms at low speed regions. In this article, we propose a modification of the frequency carriers of the CFTC-DTC of induction motors to increase the switching frequency and torque loop bandwidth by replacing the triangular-carrier-based waveform with a ramp-carrier-based waveform. The proposed method is verified by simulation and experimental results showing its excellent performances in steady-and transient-state operations.
Keywords: Alternating current motors; Direct torque control; Fixed switching frequency; Frequency carriers; Frequency limitation; High performance control; Sampling frequencies; Steady and transient state; Constant torque control; direct torque control (DTC); flux regulation; induction motor; low-speed operation